Looking back, moving forward : results and recommendations from the ICPD-at-15 process (UNFPA New YorkUS, 2010)
Provides insights into the ICPD-at-15 process. Reviews the key ICPD-at-15 activities that were organised in 2009 to assess progress and to define gaps that will require further action over the next five years. Also notes the changes that have taken place, including health sector reform and the 'gender agenda' which have influenced the way in which the ICPD Programme of Action is now being implemented.
Keywords: REPRODUCTIVE HEALTH